Poteranthera inopinata (Melastomataceae), a new species from Noel Kempff Mercado National Park, Bolivia - Almeda, Frank; Pacifico, Ricardo (Phytotaxa, 2023)
Poteranthera inopinata is described as a new species that is known only from humid or seasonally inundated savannas in Noel Kempff Mercado National Park in eastern Bolivia near its border with Brazil. Line drawings, a distribution map, a recommended conservation assessment, and a discussion of morphologically similar genera and species are provided. This new species can be recognized by its annual habit, petiolate, 3–5-nerved leaf blades (3 ̶ 10 mm long) that are conspicuously serrate with each serration tipped with a glandular trichome ca. 1 mm long, dimetric and dimorphic androecium with prolonged pedoconnectives and inconspicuously retuse staminal appendages, and petals that are minutely and deciduously glandular-ciliolate at the margins and tipped with a persistent glandular trichome 0.5 ̶ 0.75 mm long. The new species is compared with P. warmingii, its apparent closest relative, and an updated key is provided to the six recognized species of Poteranthera.